Small fixed-wing UAV Precision Aerial Drop capability development - Antonić Vuk; Trifković Milenko; Molović Vojimir; Milenković-Babić Miodrag (Scientific Technical Review)
Small fixed-wing unmanned aerial vehicles (UAVs) have proven themselves as invaluable assets for reconnaissance and surveillance missions. Their improvement and further development most often focuses on improved endurance, datalink range, camera capabilities etc. This paper presents a modular approach to "Vrabac" UAV improvement by integrating wing payload extensions, enabling precision aerial drop capabilities. This enables precise delivery of lethal or non-lethal payloads from the UAV at pre-determined coordinates or at a visually aquired target. Precision aerial drop software module is presented, focusing on the automated payload drop algorithm with continually calculated impact point prediction (CCIP) and UAV guidance to the continually calculated release point (CCRP). The chosen ballistics computation and control system implementation evaluates UAV flight parameters, wind direction and velocity, terrain profile etc. to achive a precise target strike. Simulated results with a parameter sensitivity analysis, as well as field test results are presented.